Breast-cancer mortality in screened versus unscreened women: Long-term results from a population-based study in Queensland, Australia. (June 2021) - Dunn, Nathan; Youl, Philippa; Moore, Julie; Harden, Hazel; Walpole, Euan; Evans, Elizabeth; Taylor, Kate; Philpot, Shoni; Furnival, Colin
Objective: In the context of a mature mammographic screening programme, the aim of this population-based study was to estimate rates of breast-cancer mortality among participants versus non-participants in Queensland, Australia. Methods: The Queensland Electoral Roll was used to identify women aged 50–65  in the year 2000 (n = 269, 198). Women with a prior history of invasive or in situ breast cancer were excluded (n = 6, 848). The study population was then linked to mammography records from BreastScreen Queensland together with the Wesley Breast Screening Clinic (the largest provider of private screening in Queensland) to establish a screened cohort (n = 187, 558) and an unscreened cohort (n = 74, 792). Cohort members were matched and linked to cancer notifications and deaths through the state-based Queensland Oncology Repository. Differences in breast-cancer mortality between the two cohorts were measured using Cox proportional hazards regression. Results: After 16 years of follow-up, women in the screened cohort showed a 39% reduction in breast-cancer mortality compared to the unscreened cohort (HR = 0.61, 95%CI = 0.55–0.68). Cumulative mortality over the same period was 0.47% and 0.77% in the screened and unscreened cohorts, respectively. Conclusions: This study found a significant reduction in breast-cancer mortality for women who participated in mammographic screening compared to unscreened women. Our findings of a breast-cancer mortality benefit for women who have mammographic screening are in line with other observational studies.